2002
DOI: 10.1080/09553000110106027
|View full text |Cite
|
Sign up to set email alerts
|

Mononuclear cell adhesion and cell adhesion molecule liberation after X-irradiation of activated endothelial cells in vitro

Abstract: Modulation of E-selectin liberation on activated endothelial cells may be one mechanism to decrease leukocyte adhesion after low-dose irradiation in vitro, and could be involved in the therapeutic action of anti-inflammatory radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 24 publications
9
71
0
3
Order By: Relevance
“…Although experimentally not addressed in the present investigation, it is tempting to assume that modulation of NF-κB activity and adhesion molecule expression contributes to the regulation of the adhesion process following ROS scavenging by NAC or activation of Nrf2 by AI-1 in EA.hy926 ECs. This assumption is further supported both by previous data on a nonlinear induction of NF-κB DNA binding and transcriptional activity and an altered surface expression of E-selectin contributing to a reduced mononuclear cell adhesion in EA.hy926 EC following 0.5 Gy irradiation [9,31,34]. Moreover, there is growing evidence of a tight crosstalk between the Nrf2 and NF-κB pathway with both antagonistic and synergistic effects occurring [3].…”
Section: Compliance With Ethical Guidelinessupporting
confidence: 71%
See 2 more Smart Citations
“…Although experimentally not addressed in the present investigation, it is tempting to assume that modulation of NF-κB activity and adhesion molecule expression contributes to the regulation of the adhesion process following ROS scavenging by NAC or activation of Nrf2 by AI-1 in EA.hy926 ECs. This assumption is further supported both by previous data on a nonlinear induction of NF-κB DNA binding and transcriptional activity and an altered surface expression of E-selectin contributing to a reduced mononuclear cell adhesion in EA.hy926 EC following 0.5 Gy irradiation [9,31,34]. Moreover, there is growing evidence of a tight crosstalk between the Nrf2 and NF-κB pathway with both antagonistic and synergistic effects occurring [3].…”
Section: Compliance With Ethical Guidelinessupporting
confidence: 71%
“…When assaying the functional consequences of ROS induction and Nrf2 expression in EA.hy926 ECs, we observed that, after pretreatment with both the ROS scavenger NAC and the Nrf2 activator AI-1, there was an abolishment of the diminution of PBMC adhesion to ECs following a 0.5-Gy exposure [9,35]. Indeed, growing evidence has emerged that ROS are involved in cellular adhesion to surfaces [5] as well as in monocyte binding to ECs [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, another study did not detect expression of this molecule in wild-type or in P-selectin deficient mice after abdominal irradiation at different doses (4, 10 Gy) and time (2 h or 24 h) points [6] . Recent studies have suggested that E-selectin could be involved in the antiinflammatory response after radiotherapy, mediating the drop in leukocyte adhesion after low dose irradiation (0.3-0.6 Gy) in vitro [20] .…”
Section: Molecular Determinants Of Leukocyte-endothelial Cell Adhesiomentioning
confidence: 99%
“…RT has a dual effect, inducing the production of pro-inflammatory citokines at high-doses per fraction while the opposite effect has been shown at low-doses per fraction. [2][3][4][5][6][7] Excellent reviews have been published on the pathogenesis, clinical manifestations and treatment of ophtalmopathy and Graves' disease. 8 This review is restricted to data related with the possible use of low-dose per fraction (<1 Gy/day) and low-dose RT (LD-RT) (<10 Gy total dose).…”
Section: Introductionmentioning
confidence: 99%